(3QSGdI aj Yde GdRGjQLIs - (3YHO GdMb Hf EHQGgje Hf eMeO Hf fUQ GHf SHYjf GdETHjdj GdeQSj GdnqQbhWj, bWH GdOjf CHh eMeO,J (B669 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEf GdWQjbI GdJSGYjI ai Yde GdRGjQLI GdMQajI jSJNQL efgG LhGH cd SGFd s
(3BNQgG (B:s
(3dGJVY ajg cd MQa eTO hef MQajf Hd ef MQa hGMO dGZjQ HNdGa GdChd hgh GUd JGe hGddg GYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B90s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3QjGVi (B109) s
Keywords: (3GdMQha h GdChaGbs